Impacts sociaux potentiels - Lipner, M.E. (CIPEA, 1992)
This paper briefly discusses the major themes that comprise social impact assessment. It's intended to serve as a guide-post, that is, to raise questions about how a centre such as ILCA which is mandated to work on long term problems, maintains its focus on impact, is responsive to the needs of an identified client and moves toward its ultimate goal "to discover or revise facts (research) that have practical, beneficial application (development)". Presents three case studies, namely, technology generation and impact, improved milk processing in the Ethiopian highlands, and hay making by the Borana of southern Ethiopia.